Equivalence Analysis of Mass-matching of Simulated Space Manipulator Based on Certain Quality. (October 2020) - Feng, W; Li, CH X; Wang, CH X; Ying, W M; Guo, X
Abstract: Space manipulator is a high level of integrated space of mechanical and electrical systems in mechanical, electrical, thermal and control fields. Before the experiments, it's necessary to use a simulated manipulator to verify the reliability of a zero-gravity test system. To assure the consistency between a simulated manipulator and a space manipulator, the mass and barycenter of a simulated manipulator need to be matched. In this paper, an equivalent method based on constant mass is proposed, which can quickly adjust the position of the center of mass of the simulated Space Manipulator joint and achieve the desired objective. Firstly, the fan-shaped and notched counterweights are designed to meet the adjustment requirements of radial and axial barycenter. Then, the joint barycenter models of different types of counterweights are established, and a barycenter equivalence optimization scheme based on constant mass is proposed. Through the design scheme of this paper, the quality and center of mass meet the requirements, and the experimental verification of the simulation manipulator is realized.